Legal Responsibilities of Educational Institutions in Ensuring Data Protection and Quality Learning in Digital Education Using Smartcampus - Amrin Nurfieni; Dian Ferricha; Ahmad Gelora Mahardika (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2025)
The digital transformation in education has driven the increased use of digital platforms across higher education institutions. The COVID-19 pandemic accelerated the adoption of technologies such as the Internet, big data, artificial intelligence (AI), and cloud computing in educational services, facilitating accessibility and innovation in learning. However, this development also presents significant challenges regarding the legal responsibilities of educational institutions, particularly in safeguarding personal data privacy and maintaining the quality of digital education. This study aims to identify and analyze the legal responsibilities of educational institutions in using digital platforms. A normative legal research method was applied to examine the applicable regulations, including Law No. 20 of 2003 on the National Education System, Law No. 11 of 2008 on Electronic Information and Transactions, and Law No. 27 of 2022 on Personal Data Protection. The findings reveal that educational institutions are legally obligated to ensure data privacy, uphold quality standards in education, and adhere to relevant regulations. The study recommends policies to enhance data security, develop quality content, and provide continuous training for educators to support legal compliance in digital-based learning.